The factorial structure of the Suicide Intent Scale: a comparative study in clinical samples from 11 European regions. - Antretter, E; Dunkel, D; Haring, C; Corcoran, P; De Leo, D; Fekete, S; Hawton, K; Kerkhof, A; Lönnqvist, J; Renberg, E; Schmidtke, A; Van Heeringen, K; et al. (2008)
Although the Suicide Intent Scale (SIS) is a widely used instrument in research on suicidal behavior, comparative research on the latent structure of the SIS has been neglected. To determine whether a general factor model of the SIS is supported, alternative factor models of the SIS were evaluated comparatively in 11 clinical samples. The SIS was applied as part of a structured clinical interview to patients after an episode of non-fatal suicidal behavior. The samples were drawn from 11 study centers within the frame of the WHO/EURO multicenter study on suicidal behavior. Three different two-factor and two three-factor models of the SIS were examined in each sample using principal component analysis with orthogonal Procrustes rotation. The factorial structure of the 'subjective part' of the SIS (items 9-14) was strongly supported, whereas an acceptable model fit for the 'objective part' was not found. Possible future revisions of 'objective' SIS items may be worth consideration. As a limitation, the results of the study might not generalize to other samples that use different definitions of non-fatal suicidal behavior.